PENINGKATAN PEMAHAMAN KONSEP SISWA DENGAN MODEL DISCOVERY LEARNING DIPADU LESSON STUDY PADA MATERI KPK DAN FPB - Oktaviana, Dwi; Astuti, Tri; Nurhazannah, Yunie; Indaryati, Fitriah; Aswad, Asnawi; Harpiani, Harpiani; Muniroh, Muna (IAIN Pontianak, 2023)
The aim of this research is to describe the increase in students' ability to understand concepts using the discovery learning model through lesson study on KPK and FPB material. This research is an experimental research with a one group pretest-posttest design. The sample in this research was class VIIC students at SMP Negeri 13 Pontianak using a purposive sampling technique of 32 people. The research results showed that students obtained pretest and posttest scores for understanding concepts in KPK and FPB material with an average of 62,97 and 84,69. After implementing learning using the discovery learning model through lesson study, students' conceptual understanding of the KPK and FPB material received a Sig. (2 tailed) = 0.000 with Sig. (2 tailed) < 0.05 (0.000 > 0.05) then Ho is rejected. Thus, through lesson study, the application of the discovery learning model to KPK and FPB material can increase students' understanding of concepts.